Pendidikan Salaf dan Inovasi Modern dalam Kurikulum Pesantren - Ana Kurnia Azhari; Puput Anggraini; Luluk Rosyidatul Ummah; Ainur Rofiq (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The main purpose of this research is to provide effective solutions in integrating Salaf education and modern innovations in the pesantren curriculum, so as to improve relevance, quality. The object of this research on Salaf education and modern innovations in the pesantren curriculum is located at Darussalam Blokagung Islamic boarding school. Darussalam Blokagung Islamic boarding school is known as one of the leading Islamic boarding schools that has long implemented Salaf education. The design of the research on Salaf Education and Modern Innovations in the Pesantren Curriculum, the method used is a qualitative technique with a case study approach. The data collection techniques in this research are observation, interview and documents. Data collection techniques in this study were observation, interviews and documents. Data analysis in this study used the Spradley model, which is known for its in-depth and systematic approach to understanding culture. This model consists of four stages, namely domain analysis, taxonomy, components, and cultural themes, each of which serves to identify and organize information in a structured way. The results of this research on Salaf Education and Modern Innovation in Pesantren Curriculum resulted in Dynamic Curriculum in Pesantren Education, Critical Learning Module Innovation in Islamic Thought Studies, and Innovation Lab Development for Exploration of Islamic Values through Technology.